2004
DOI: 10.1103/physrevd.69.015011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the neutralino system in two-body decays of neutralinos

Abstract: In the minimal supersymmetric standard model ͑MSSM͒, the neutralinos, the spin-1/2 Majorana superpartners of the neutral gauge and Higgs bosons, are expected to be among the light supersymmetric particles that can be produced copiously at future high-energy colliders. We analyze two-body neutralino decays into a neutralino plus a Z boson or the lightest neutral Higgs boson h, allowing the relevant parameters to have complex phases. We show that the two-body tree-level decays of neutralinos are kinematically al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Note that also the diagonal elements, being CP even quantities, are changed for ϕ M 1 = 0 and ϕ µ = 0. This fact has been exploited in [10] as a possibility to determine the CP violating phases.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that also the diagonal elements, being CP even quantities, are changed for ϕ M 1 = 0 and ϕ µ = 0. This fact has been exploited in [10] as a possibility to determine the CP violating phases.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…with the subsequent two-body decay of one neutralino into the Z boson (for recent studies see [9,10])…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the Majorana nature of neutralinos have been performed [8,9,10,11]. Reference [9] observed that the CP and CP T properties of the final state determine the Majorana nature of neutralinos in the process e + e − →χ 0 1χ 0 i → ℓ + ℓ −χ0 1χ 0 1 (i = 2, 3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Selectron pair production in e − e − scattering, e − e − →ẽ −ẽ− , would also be of great utility, as it could proceed only on account of t-channel Majorana neutralino exchange [10]. In addition, Majorana effects in two-or three-body decays of neutralinos are known to exist [11].…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose, it will be crucial to measure their quantum numbers and to confirm that they are indeed Majorana fermions [4,5,6,7]. Moreover, masses, mixings, couplings and CP violating phases must be measured in a model-independent way [8,9,10] to reconstruct the fundamental SUSY parameters and to verify the SUSY relations at the electroweak scale, leading to a reliable extrapolation to the grand unification scale or the Planck scale [11].…”
Section: Introductionmentioning
confidence: 99%